Synthesis , Characterization , Antimicrobial and antioxidant of Studies New 5,5’-((1,4-phenylenebis(methanylylidene))bis(azanylylidene))bis(1,3,4-thiadiazole-2(3H)-thione) With some transition metal ions - kareem, Zainab M.; Naser, Hameedi N. (International Journal of Psychosocial Rehabilitation, 2020)
A new ligand 5,5’-((1,4-phenylenebis(methanylylidene))bis(azanylylidene))bis(1,3,4-thiadiazole-2(3H)-thione) and its Cr(IIl) , Co(ll) and Cu (ll) complexes were synthesized . the new ligand and its complexes have been characterization on the basis their spectra of H1NMR, mas, Fourier transform infrared (FTIR), as well as magnetic susceptibility, elemental analysis [C,H,N,S], atomic absorption and conductance measurements. The program of Hyperchem 8 have been used for theoretical accounts using PM3 method to study the electrostatic potential that provided good information about the complexity site. Of the result obtained we can suggested octahedral geometries for Cr(ІІІ), tetrahedral geometry for Co(ІІІ) and square planer geometry for Cu(ІІ). The antioxidant activity of ligand was evaluated by DPPH scavenger and the ligand was showed high antioxidant activity. The ligand and its complex gave a good activity antibacterial.